2015
DOI: 10.9758/cpn.2015.13.1.83
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Levetiracetam in Cognitive Performance in Healthy Individuals: Neuropsychological, Behavioral and Electrophysiological Approach

Abstract: ObjectiveThe present study sought to analyze the influence of Levetiracetam (LEV) in cognitive performance by identifying the changes produced by LEV in reaction time, in neuropsychological assessment of attention and memory and in absolute theta power in frontal activity.MethodsTwelve healthy subjects (5 men and 7 women; mean age, 30.08 years, standard deviation, 4.71) were recruited for this study. The neuropsychological tests: Trail Making Test (A and B), Digit Span (direct and indirect numerical orders/wor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 77 publications
2
21
0
Order By: Relevance
“…This is in agreement with previous studies that have reported improvement in cognitive functions in patients treated with LEV as monotherapy. 18,19 In the current study, it was found that there were highly significant improvements in attention and concentration measured by the WCST in the LEV group, in agreement with Noh et al, who found improvement in domains of cognition in patients treated with LEV as monotherapy. 20 Furthermore, that a highly significant improvements in processing speed, mental flexibility, and executive functioning on trail-making tests A and B in the LEV group compared to the VPA group were demonstrated, in agreement with previous studies 21,22 finding that both trail-making test A and reaction-time results showed significant differences with LEV treatment.…”
Section: Discussionsupporting
confidence: 91%
“…This is in agreement with previous studies that have reported improvement in cognitive functions in patients treated with LEV as monotherapy. 18,19 In the current study, it was found that there were highly significant improvements in attention and concentration measured by the WCST in the LEV group, in agreement with Noh et al, who found improvement in domains of cognition in patients treated with LEV as monotherapy. 20 Furthermore, that a highly significant improvements in processing speed, mental flexibility, and executive functioning on trail-making tests A and B in the LEV group compared to the VPA group were demonstrated, in agreement with previous studies 21,22 finding that both trail-making test A and reaction-time results showed significant differences with LEV treatment.…”
Section: Discussionsupporting
confidence: 91%
“…[6][7][8] The few available clinical studies on levetiracetam (LEV) have not shown significant side effect on the endocrine function, 9 but rather allude to the neuroprotective effect and excellent pharmacokinetic profile as significant factors in explaining the improved quality of life among those on LEV compared carbamazepine (CBZ). [9][10][11] There is however growing evidence from animal studies supporting possible role of LEV in reproductive toxicity with oxidative stress, hormonal alterations, presence of synaptic vesicle protein receptors in the synaptic vesicle of glycoprotein family on the gonads and endocrine cells apart from central nervous system as possible mechanism. [12][13][14] This study is aimed at comparing occurrence of PCOS among Nigerian WWE taking CBZ and LEV.…”
Section: Introductionmentioning
confidence: 99%
“…Levetiracetam has been demonstrated to modulate cognitive functions and this effect has been related to theta oscillations 56 ; however, there are no published results on gamma oscillations.…”
Section: Spontaneous Cortical Oscillations To Investigate the Effectsmentioning
confidence: 99%